Prophetic leadership as a solution for the implementation of sharia maqosid. - Abdussalam Alghozali; Hasiolan Nasution; Lutfi (Journal of Islamic, Social, Economics and Development, 2024)
This study aims to determine the effect of prophetic leadership on the implementation of maqosid shari'at. The methodology used in the research is a qualitative method with a literature review approach. Prophetic leadership has several elements of leadership, namely pious leadership, knowledgeable leadership, strong leaderrship, trustworthy leadership, generative leadership. Leadership that is not only worid-orientated, but also focuses on the afterlife. The crises that are being faced by the people are humanitarian crises, an economic crisis, and moral crises. Prophetic leadership is a term that refers to a leadership style that promotes spiritual and moral values, referring to the example shown by prophets in religious history. Prophetic leadership is a process that aims to manage, direct and influence others sincerely and sincerity supported by the morals exemplified by the Prophet Prophet PBUH. Another form of prophetic leadership is in the form of liberation, humanization, and transdence. Some of the prophetic leadership traits that emerge are justice, wisdom, empathy and care. Maqosid shari'at becomes the purpose of leadership, namely to protect religion, protect offspring, protect property, protect tea mind, and protect the soul. Islamic laws during the prophetic period were dynamic, flexible, and universal. There are 228 verses of the Qur'an that regulate social matters. The succes of prophetic leadership is proven by the glory of Islam for 14 centuries the world.